Experiments revealing the formation of refractory methylmercury pools in natural sediments and soils. (1st July 2022) - Baptista-Salazar, Carluvy; Liem-Nguyen, Van; Jonsson, Sofi
Abstract: Methylation and demethylation of mercury (Hg) are well recognized as processes controlling the concentrations of monomethylmercury (MeHg) in natural environments, and thus the pool of Hg available for biological uptake. In addition, studies have indicated the potential role of refractory MeHg pools (not readily available for demethylation) on the pool of MeHg in, for example, sediments and soils. These studies, however, remain scarce and often the role of refractory MeHg pools is overlooked. Here, we have conducted incubation experiments aiming to quantify refractory MeHg pools in contrasting environments. In our study, sediments (from lakes and brackish seawater sites) and soils (from forests and marshes) were incubated with isotopically enriched Hg tracers (Me 201 Hg and 198 Hg) for up to 6 weeks. To follow the potential formation of refractory MeHg pools, %MeHg (fraction of Hg occurring as MeHg) after the first week of incubation for the added 198 Hg and Me 201 Hg tracers, and ambient Hg was compared. The high %MeHg for the 198 Hg tracer compared to the %MeHg of ambient Hg suggests a higher initial availability of added 198 Hg in comparison to the ambient Hg in the sediments. For the soils, low %MeHg for the 198 Hg tracer suggests low Hg methylation rates. The discrepancy observed between the sediments and soils can be explained by a higher availability of inorganic Hg in the sediments, as suggested by the Hg thermal fractional analysis conducted. The %MeHg steady state for the added Me 201 Hg tracer remained high (>17%) throughout the experiment, suggesting refractory pools of MeHg to be built-up in all tested sediments and soils. Together, the %MeHg for the added Hg tracers demonstrate that a significant fraction of the MeHg produced in sediments and soils is sequestered into refractory pools not readily available for demethylation. Furthermore, these results show that conditions favoring net methylation in sediments and soil could result in elevated concentrations of MeHg for a significant amount of time (months) even if the conditions favoring Hg net methylation are only temporary.